Pan-Neuronal Expression of APL-1, an APP-Related Protein, Disrupts Olfactory, Gustatory, and Touch Plasticity in Caenorhabditis elegans - Ewald, Collin Y. (Society for Neuroscience, 2012)
Patients with Alzheimer's disease show age-related cognitive decline. Postmortem autopsy of their brains shows the presence of large numbers of senile plaques, whose major component is the β-amyloid peptide. The β-amyloid peptide is a cleavage product of the amyloid precursor protein (APP). In addition to the neurodegeneration associated with β-amyloid aggregation in Alzheimer's disease patients, mutations in APP in mammalian model organisms have also been shown to disrupt several behaviors independent of visible amyloid plaque formation. However, the pathways in which APP function are unknown and difficult to unravel in mammals. Here we show that pan-neuronal expression of APL-1, the Caenorhabditis elegans ortholog of APP, disrupts several behaviors, such as olfactory and gustatory learning behavior and touch habituation. These behaviors are mediated by distinct neural circuits, suggesting a broad impact of APL-1 on sensory plasticity in C. elegans. Furthermore, we found that disruption of these three behaviors requires activity of the TGFβ pathway and reduced activity of the insulin pathway. These results suggest pathways and molecular components that may underlie behavioral plasticity in mammals and in patients with Alzheimer's disease.